2006
DOI: 10.18084/1084-7219.11.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Research to Life: Using Social Work Students in a Statewide Foster Care Census

Abstract: A review of historical developments in child welfare and social work research reveals continuing challenges for social work education. This article describes a collaborative effort to conduct a statewide survey of children in foster care. Social work students from eight universities helped to complete a state-wide census of foster care families in collaboration with child welfare agencies and the Public Child Welfare Consortium. The article discusses the impetus and scope of the project, as well as the benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…For example, Holley et al (2007) established that including research projects in research classes increases students' confidence. Similarly, Lundahl's (2008) study confirmed that involvement in a research project increased student confidence and appreciation for research as related to practice as did Smith and Gore's (2006) study involving student involvement. Similarly, Morgenshtern et al (2011) found that social work student attitudes toward research improved positively after hands-on experiences.…”
Section: Discussion Commonalitiessupporting
confidence: 52%
“…For example, Holley et al (2007) established that including research projects in research classes increases students' confidence. Similarly, Lundahl's (2008) study confirmed that involvement in a research project increased student confidence and appreciation for research as related to practice as did Smith and Gore's (2006) study involving student involvement. Similarly, Morgenshtern et al (2011) found that social work student attitudes toward research improved positively after hands-on experiences.…”
Section: Discussion Commonalitiessupporting
confidence: 52%
“…Although direct benefits of collaborative research to undergraduate students have been well documented, [22][23][24] benefits and challenges specific for social work faculty and students have only recently begun to be explored. 25,26 An early, exploratory study of social work faculty identified several key benefits, as well as risks of faculty-student collaboration, such as situations where the student performs all or most of the work but receives little to no credit. 27 In an effort to reduce risks, Barretta-Herman and Garrett 27 suggest that faculty-student collaborators utilize written agreements clarify expectations.…”
Section: • Collaborative Research: Benefits and Challengesmentioning
confidence: 99%
“…Since that time, with a growing emphasis on evidence-based practice, there has been an influx of articles offering specific models and methods for teaching research and supporting student participation in research (Dietz et al, 2004;Jacobson & Goheen, 2006;Rubin & Parrish, 2007b;Smith & Gore, 2006), but few if any explorations of the breadth and type of research education taking place across curricula and various levels of education.…”
Section: Journal Of Social Work Educationmentioning
confidence: 99%